Assessing the implications of water harvesting intensification on upstream–downstream ecosystem services: a case study in the Lake Tana basin - Dile, Y.T.; Karlberg, L.; Daggupati, P.; Srinivasan, R.; Wiberg, David A.; Rockström, Johan (Elsevier, 2016)
Water harvesting systems have improved productivity in various regions in sub-Saharan Africa. Similarly, they can help retain water in landscapes, build resilience against droughts and dry spells, and thereby contribute to sustainable agricultural intensification. However, there is no strong empirical evidence that shows the effects of intensification of water harvesting on upstream–downstream social–ecological systems at a landscape scale. In this paper we develop a decision support system (DSS) for locating and sizing water harvesting ponds in a hydrological model, which enables assessments of water harvesting intensification on upstream–downstream ecosystem services in meso-scale watersheds. The DSS was used with the Soil and Water Assessment Tool (SWAT) for a case-study area located in the Lake Tana basin, Ethiopia. We found that supplementary irrigation in combination with nutrient application increased simulated teff (Eragrostis tef, staple crop in Ethiopia) production up to three times, compared to the current practice. Moreover, after supplemental irrigation of teff, the excess water was used for dry season onion production of 7.66 t/ha (median). Water harvesting, therefore, can play an important role in increasing local- to regional-scale food security through increased and more stable food production and generation of extra income from the sale of cash crops. The annual total irrigation water consumption was ~ 4%–30% of the annual water yield from the entire watershed. In general, water harvesting resulted in a reduction in peak flows and an increase in low flows. Water harvesting substantially reduced sediment yield leaving the watershed. The beneficiaries of water harvesting ponds may benefit from increases in agricultural production. The downstream social–ecological systems may benefit from reduced food prices, reduced flooding damages, and reduced sediment influxes, as well as enhancements in low flows and water quality. The benefits of water harvesting warrant economic feasibility studies and detailed analyses of its ecological impacts.